Meningkatkan Pemahaman Sains Pada Anak Usia Dini Kelompok B dengan Pendekatan Metode PJBL Melalui Eksperimen - Nuri Arifiah Romadhoni; Ruqoyyah Fitri; Nurul Khotimah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to understand science learning in children, emphasizing the use of the PJBL approach using loss-part media that is around us. The Project Based Learning Approach (PJBL) is a learning method that allows students to learn through real projects or assignments that require problem solving. PJBL learning can provide an interesting and meaningful learning experience for children. The application of learning is product-oriented. Research uses the method Qualitative, sources of information obtained from direct work practice. Research findings show that the development model is used as a tool for applying understanding to ongoing material.